Surgical Treatment of Anterior Communicating Artery Aneurysms: Hints and Precautions for Young Cerebrovascular Surgeons - Sturiale, Carmelo Lucio; Ricciardi, Luca; Marchese, Enrico; Puca, Alfredo; Olivi, Alessandro; Albanese, Alessio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Anterior communicating artery (AComA) aneurysms are the most common intracranial aneurysm, accounting for 25 to 38% of all cases. In spite of the advent of modern neurointerventional treatments, they still represent a strong indication for clipping in certain anatomical and clinical conditions. However, AComA aneurysms are the deepest located aneurysms of the anastomotic circle of Willis, with a complex spatial orientation, and they are fed by bilateral branches of the anterior circulations. Although, on one hand, these aneurysms represent the most complex ones of the anterior circulation, on the other hand, the experience of young neurosurgeons is increasingly limited. Therefore, respecting operative guidelines is crucial to achieve the best aneurysm exclusion and avoid fatal intraoperative complications.Study Objective We describe the technical algorithm we use to teach young neurosurgeons how to approach AComA aneurysms and help them to develop a procedural memory needed to perform an efficient and safe surgery.Materials and Methods We reviewed our last 10 years of institutional experience of > 200 cases of clipping ruptured and unruptured AComA aneurysms, analyzing our technical refinements and the difficulties in teaching residents and young neurosurgeons how to establish fundamental key points and design a didactic algorithm that includes operative instructions and safety rules.Results We identified seven pragmatic technical key points regarding craniotomy, cisternostomy, gyrus rectus corticectomy, proximal control, perforators and Heubner preservation, aneurysm neck dissection, and clipping to use in a didactic algorithm for teaching residents and as operative instructions for inexperienced neurosurgeons.Conclusion In the setting of clipping AComA aneurysms, respect for surgical rules is of paramount importance to perform an efficacious and safe procedure and ensure the best aneurysm exclusion and preservation of neurovascular structures.
Keywords: anterior communicating artery aneurysm; AComA aneurysms; lateral supraorbital approach; gyrus rectus corticectomy; vascular neurosurgery